IbM Pendidikan Kesehatan Hipertensi dan Pengukuran Kolesterol - Diah Atmarina Yuliani; Khamidah Achyar; Isnaeni Rofiqoch (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2020)
Hypertension is a global problem that requires attention because it can caused major deaths in both developed and developing countries. According to a survey conducted by the World Health Organization (WHO) in 2000, total world population suffering from male hypertension was around 26.6% and women around 26.1% it was estimated that by 2025 the number would increase to 29.2%. Indonesia 2013 Basic Health Research showed the prevalence of PTM (non-communicable diseases) including Stroke 12.1 per 1000, Coronary Heart Disease 1.5%, Heart Failure 0.3%, Diabetes Mellitus 6.9%, Kidney Failure 0.2%, Cancer 1.4 per 1000, Obstructive Chronic Lung Disease 3.7% and Injury 8.2%. Riskesdas 2013 showed 69.6% of Diabetes Mellitus and 63.2% Hypertension were still undiagnosed. Aim of activity was to increase maternal knowledge about hypertension and know total cholesterol levels. Activity begins with a survey of the target group, coordination, licensing with related agencies, and preparation of materials and equipment. Community service activities include providing health education about hypertension and cholesterol and measuring total cholesterol levels. Follow up activities carried out results of monitoring mothers understand and understand hypertension and cholesterol are non-communicable diseases. Importance of community service is increased knowledge of mothers about some non-communicable diseases, namely hypertension and cholesterol.